2008
DOI: 10.1177/1420326x08089551
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Radionuclide Concentrations in Water Supply from Bore-holes in Ogbomosoland, Western Nigeria

Abstract: The level of radionuclide concentration in water from bore-holes in selected areas of Ogbomosoland, a region consisting of five local governments, was determined. Concentration of 238U, 232Th, and 40K was determined for the water samples from eight bore-holes around Ogbomosoland by γ-ray spectrometry with a high-purity germanium (HPGe) detector connected to a multichannel analyzer. All the water samples from these bore-holes were found to contain acceptable levels of radionuclides with mean activity values of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Also recently an annual effective dose rate of 1.64 mSv due to environmental radiation has been reported for the city [4]. Metal pollution in shallow well water samples in the neighboring town to the study areas has been reported [5], radioactivity in borehole water in neighboring state [6] and in part of Ogun State [7]. It is therefore envisaged that radionuclide concentrations may be elevated in the different food crops and the diets derivable from them.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Also recently an annual effective dose rate of 1.64 mSv due to environmental radiation has been reported for the city [4]. Metal pollution in shallow well water samples in the neighboring town to the study areas has been reported [5], radioactivity in borehole water in neighboring state [6] and in part of Ogun State [7]. It is therefore envisaged that radionuclide concentrations may be elevated in the different food crops and the diets derivable from them.…”
Section: Introductionmentioning
confidence: 90%
“…where, i denotes a food group, the coefficients U i and denote the consumption rate (kg•y -1 ) and activity concentration of the radionuclide r of interest (Bq•kg -1 ), respectively, and g T,r is the dose conversion coefficient for ingestion of radionuclide r (Sv•Bq -1 ) in tissue T. For adult members of the public, the recommended dose conversion coefficient g T,r for 40 K, 226 Ra, 228 Th, and 137 Cs, are 6.2 × 10 -9 Sv•Bq -1 , 2.8 × 10 -7 Sv•Bq -1 , 7.2 × 10 -8 Sv•Bq -1 , and 1.3 × 10 -8 Sv•Bq -1 , respectively [16]. Presently, no site specific consumption data exist in the study area and as such we have adopted the country's mean annual consumption rate per capita values ( Table 7) to enable us calculate the effective dose due intake of the food stuffs using Equation (6). Tables 3-6 for each of the crops and the diet derivatives.…”
Section: Ingestion Effective Dose Evaluationmentioning
confidence: 99%
“…The city is also witnessing aggressive construction works to provide houses for this influx of people. ome papers have been published on the radioactivity level in some regions of Nigeria like [8][9][10][11][12] and more recently on the neutron activation analysis of soil and leaf samples from different parts of Abuja Metropolis [13][14] there is, however, no data is available for radionuclides content in soil samples in this city from the survey of literature and authors' knowledge. This work therefore focuses on the measurement of decay products of the 238 U and 232 Th series as well as of the primordial radionuclide 40 K. The baseline data of this type will certainly be of importance in making estimations of population exposures.…”
Section: Introductionmentioning
confidence: 99%
“…The average value for the region is 0.8 mSv year -1 endorsed for normal environment (Arogunjo, 2007). Awodugba, (2008), determined the level of radionuclide concentration in water from boreholes in selected areas of Ogbomosoland.…”
Section: Uranium In Palm Oilmentioning
confidence: 99%